Evaluation of Training on Backyard Poultry: A Case of Entrepreneurship Development Among Small and Marginal Farmers - Surendar Kumar , R.P. Singh, Saurabh Sharma (Indian Journal of Extension Education, 2022)
An investigation was carried out during May 2011with the objective of evaluating impact of training on backyard poultry farming among small andmarginal farmers at KVK, Baghpat,Uttar Pradesh. On the basis of findings, itmay be concluded that training on disease management of chicks is most important area where training is highly required followed by improved breeding. The findings also showed that education, socio-economic status, scientific orientation, land holding, social participation and marketing intelligence having the positive correlation with an amount of knowledge gained by participant.The knowledge gained during the three days training was calculated as 114%.